2006
DOI: 10.17796/jcpd.30.3.g66h2750h11242p6
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and orofacial characteristics of children with attention-deficit hyperactivity disorder during a dental visit

Abstract: ADHD is a neuropsychological disorder, affecting attention, impulsiveness and activeness. The study included 36 children with ADHD, 47 without, and two silent observers.A dental form, SNAP-IV and ADHDT symptom checklists were used. Statistically significant differences were observed in hospitalization histories, oral habits, tongue characteristics, and facial biotype. Differences in orofacial characteristics and behavior between the groups were confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 7 publications
1
19
1
3
Order By: Relevance
“…The published literature has also suggested a higher prevalence of traumatic injuries in children with ADHD, possibly because of the nature of their functional impairments which may affect motor coordination problems (36) and peer relationships (37), and increase the risk of physical abuse (38). Studies have reported trauma prevalence ranging from 2% to 42% in 1-to 19-yr-old children with ADHD, but few studies have reported statistically significant differences from children without ADHD (17,18,(39)(40)(41). Although the numbers in the present study were too low for valid inference, falls and collisions were the most frequently reported cause of trauma, followed by sports-related incidences, which is similar to existing studies (42).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The published literature has also suggested a higher prevalence of traumatic injuries in children with ADHD, possibly because of the nature of their functional impairments which may affect motor coordination problems (36) and peer relationships (37), and increase the risk of physical abuse (38). Studies have reported trauma prevalence ranging from 2% to 42% in 1-to 19-yr-old children with ADHD, but few studies have reported statistically significant differences from children without ADHD (17,18,(39)(40)(41). Although the numbers in the present study were too low for valid inference, falls and collisions were the most frequently reported cause of trauma, followed by sports-related incidences, which is similar to existing studies (42).…”
Section: Discussionsupporting
confidence: 82%
“…Bruxism has also frequently been associated with ADHD , although only a few studies have reported on clinical attrition wear. The present study found a significantly higher number of parental‐reported tooth‐grinding habits among children with ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, high levels of STS expression in the thalamus, basal ganglia and cerebellar neuroepithelium (which gives rise to GABAergic and glutamatergic neurons of the cerebellum; Hoshino et al 2005) were of particular interest, given prior data suggesting aberrant development of these regions in both ADHD (Dickstein et al 2006;Perlov et al 2009;Silk et al 2009;Valera et al 2007) and schizophrenia (Ellison-Wright & Bullmore 2010;Maloku et al 2010). Similarly, altered STS function in the hypothalamus/pituitary gland, olfactory epithelium and tongue could feasibly play a role in the altered hypothalamic-pituitary-adrenal axis responsivity (van West et al 2009), odor detection abnormalities (Karsz et al 2008;Romanos et al 2008) and tongue characteristics (Atmetlla et al 2006) previously described in ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…DEHB'li çocukların sağlıklı çocuklarla karşılaştırıldığı bir çalışmada tırnak yeme ve bruksizm gibi kötü oral alışkanlıkların DEHB grubunda daha yaygın olduğu bildirilmiştir (71). DEHB'li çocuklarda bruksizmin, stimülan ilaçların yan etkisi olarak da ortaya çıkabileceği unutulmamalıdır (29,72).…”
Section: Dikkat Eksikliği Ve Hiperaktivite Bozukluğu Ve Parafonksiyonunclassified